Subsea engineering handbook - Bai, Yong (Gulf Professional Pub., 2010)
Designing and building structures that will withstand the unique challenges that exist in Subsea operations is no easy task. As deepwater wells are drilled to greater depths, engineers are confronted with a new set problems such as water depth, weather conditions, ocean currents, equipment reliability, and well accessibility, to name just a few. A definitive reference for engineers designing, analyzing and instilling offshore structures, Subsea Structural Engineering Handbook provides an expert guide to the key processes, technologies and equipment that comprise contemporary offshore structure.